Sweden's Energy Investment Challenge - Pär Holmberg; Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2021)
Sweden faces a major challenge in the next decades because of a projected increase in electricity demand, aging supply infrastructure and the transition to an energy system with a substantial share of weather-dependent production. This paper discusses the incentives to invest in production capacity in the Swedish electricity market, the energy policies that drive the development and proposes changes in market design to cope with this energy investment challenge.
Keywords: D25; D47; Q40; Q48; 330; Energy policy; Energy transition; Market design; Reliability; Resource efficiency